Beispiel Nr: 25
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-1\frac{1}{2}/0)\qquad Q(2/0) \\\\ \\ \textbf{Rechnung:} \\ P(-1\frac{1}{2}/0)\qquad Q(2/0) \qquad a=\frac{1}{3} \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=\frac{1}{3}(x+1\frac{1}{2})(x-2)\\ y=\frac{1}{3}(x^2+x \cdot 1\frac{1}{2} +\left(-2\right)\cdot x +1\frac{1}{2}\cdot \left(-2\right) )\\ y=\frac{1}{3}(x^2 -\frac{1}{2} x-3) \\ y= \frac{1}{3}x^2-\frac{1}{6}x-1 $